PERAN BAZNAS KOTA SURABAYA DALAM MENINGKATKAN ANGKA PARTISIPASI SEKOLAH DAN PESANTREN - roudhotun roudho; Lilik Huriyah (STKIP Subang, 2025)
BAZNAS Surabaya City, as the official institution that manages zakat, plays a vital role in improving community welfare, particularly through education. This study aims to explain the role of BAZNAS Surabaya City in increasing the number of children attending school and attending Islamic boarding schools through various educational programs based on zakat, infaq, and alms (ZIS). This study uses a descriptive qualitative approach with data collection methods through interviews, observation, and documentation. The results show that BAZNAS Surabaya City has implemented various programs such as Smart Surabaya, a monthly educational assistance program for junior high school (SMP) or MTs (Islamic junior high school) students and Islamic boarding schools. The program is based on the principle of ZIS fund management to realize social justice in education. The impact is seen in increased access to education for children from families in need of assistance and the increasing activity of Islamic boarding schools in developing religious and independent human resources. However, BAZNAS Surabaya City still faces obstacles in terms of equitable program coverage, effectiveness in distributing assistance, and limited resources. Therefore, more thorough program planning, collaboration with various sectors, and optimal use of digital technology in zakat management are needed so that its benefits can be expanded and sustained.